2022
DOI: 10.1038/s41598-022-06626-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between domains of flourishing

Abstract: The longitudinal interrelationships between domains of human well-being or flourishing remain understudied empirically. While different aspects of flourishing may be sought as their own end, it is also the case that well-being in one domain may influence well-being in other domains. Using longitudinal data form a sample of employees from a large national employer in the United States (N = 1209, mean age = 43.52 years, age range 20–74 years), this study examined the temporal associations between various domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 73 publications
0
19
0
1
Order By: Relevance
“…In our exploratory work of various character items (cf. Chen et al, 2020; Lee et al, 2021) that is roughly based on a conceptualization of the cardinal virtues of practical wisdom, justice, fortitude and temperance, as well as more global character items, we have found the achieving of these three criteria above not entirely straightforward. Of the various items we have considered, only one, relatively global, character item has clearly and consistently been predictive of an individual’s own subsequent well-being outcomes.…”
Section: Evaluating Character Item Successes and Failures And Other A...mentioning
confidence: 83%
See 2 more Smart Citations
“…In our exploratory work of various character items (cf. Chen et al, 2020; Lee et al, 2021) that is roughly based on a conceptualization of the cardinal virtues of practical wisdom, justice, fortitude and temperance, as well as more global character items, we have found the achieving of these three criteria above not entirely straightforward. Of the various items we have considered, only one, relatively global, character item has clearly and consistently been predictive of an individual’s own subsequent well-being outcomes.…”
Section: Evaluating Character Item Successes and Failures And Other A...mentioning
confidence: 83%
“…Longitudinal associations of responses to other character items with other aspects of subsequent well-being were somewhat more mixed after control for other variables, mostly with no association whatsoever for a number of other subsequent well-being outcomes (Chen et al, 2020). Some item responses even manifested a negative association with certain aspects of subsequent well-being.…”
Section: Evaluating Character Item Successes and Failures And Other A...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the analyses, we included a domain specific score reflecting overall social connectedness. We also used each of the seven items of the social connectedness domain as an independent variable separately [these variables were applied as standardized continuous variables (mean = 0, standard deviation = 1)], as prior research showed that longitudinal associations between overall flourishing and individual items of social connectedness vs. overall social connectedness score yielded different results [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate comparison of effect estimates across continuous outcomes, we standardized all continuous outcomes (M = 0, SD = 1). We applied Bonferroni corrections to account for multiple testing, but we focus our interpretation on results before Bonferroni correction because practices for multiple testing vary and continue to evolve [44][45][46] . However, to acknowledge the different practices and cutoffs that can be applied, all tables that include the results of multivariable analyses report p-values both before and after Bonferroni correction.…”
Section: Studymentioning
confidence: 99%